Faktor-Faktor yang Mempengaruhi Penghindaran Pajak pada Perusahaan Food and Beverage - Lucia Ari Diyani; Huda Aulia Rahman (Universitas Prasetiya Mulya, 2022)
This study aims to examine the effect of advertising expense, capital intensity, and sales growth on tax avoidance and uses firm size as a moderating variable. The research population comes from the food & beverage sector which is one of the government's priorities as a driving force for the national economy. The company is listed on the Indonesia Stock Exchange for eight periods, namely 2013-2020. This research is a causal research and uses quantitative methods which are processed using panel data regression analysis techniques. The results show that sales growth has a positive impact on tax avoidance, while advertising expenses and capital intensity have no impact. Then, company size is only able to moderate the effect of sales growth on tax avoidance.